Evaluating the Functional Efficiency Improvement of RSUD dr. Loekmono Hadi Kudus Website Redesign Using Black Box Testing - Musannadah, Siti; Gustalika, Muhamad Azrino (IJOEM Indonesian Journal of E-learning and Multimedia, 2025)
Background: Hospital websites are vital for public health information access. The previous RSUD dr. Loekmono Hadi Kudus website had significant usability and functional issues, with many features being non-operational, necessitating a redesign for better quality and user engagement.Aims: This research assesses the improvement in functional efficiency of the RSUD dr. Loekmono Hadi Kudus website post-redesign, focusing on a quantitative comparison of functional integrity between the old and new versions through Black Box testing.Methods: The website redesign followed the Design Thinking approach, focusing on understanding user needs and developing empathetic, user-centered solutions. Functional efficiency was evaluated through Black Box testing on ten core features representing the hospital website’s main functionalities: (1) homepage navigation links, (2) automatic banner slide, (3) manual banner navigation buttons, (4) “About Us” dropdown, (5) main “Doctor” menu, (6) doctor search feature, (7) “Doctor Schedule” access, (8) “Facilities” dropdown, (9) detailed facility information access, and (10) “Service Tariff” dropdown for transparent service fee information.Result: Black Box testing showed a profound improvement in functional efficiency. The redesigned website achieved 100% functional validity for all 10 tested features, a significant rise from the original's 30% operational rate for the same features.Conclusion: Strategic Design Thinking application, meticulous development, and rigorous testing significantly enhanced the RSUD dr. Loekmono Hadi Kudus website's functional efficiency from 30% to 100%, enhancing reliable function execution and fostering better human-computer interaction.